A blue arsenomolybdic acid-crystal violet ion-associate pair paving the way for the field detection of arsenic in groundwater. Issue 36 (26th August 2022) - Krishna, M. V. Balarama; Thangavel, S.; Sunitha, Y.; Sanjiv Kumar,
Abstract : A simple visual colorimetric method based on arsenomolybdic acid-crystal violet ion-associate pair formation is described for the detection of As in groundwater at about 10, 25 and 50 μg L −1 levels. Abstract : A simple visual colorimetric method based on arsenomolybdic acid-crystal violet ion-associate pair formation is described for the detection of As in groundwater at about 10, 25 and 50 μg L −1 levels. The pair exhibits light green coloration at ≤5 μg L −1 and blue colorations of distinctly different intensities at about 10, 25 and 50 μg L −1 concentrations of arsenic. High sensitivity is achieved by the preconcentration of As that entails simultaneous sorption of both As(iii ) and As(v ) from groundwater on covellite (CuS) and, later, their elution as As(v ), which subsequently participates in the formation of arsenomolybdic acid. The interference in the color development from PO4 3− ions that are as efficiently sorbed on CuS and eluted as the oxyanions of As is eliminated by their selective removal by Ce 4+ ions under basic (pH ∼ 8.5) conditions. The removal is caused by the formation of cerium phosphate and its co-precipitation with calcium hydroxide. SiO4 2− ions do not interfere in the process as they are not sorbed by CuS. Groundwater containing ≤0.5 mg L −1 P and ≥200 mg L −1 total dissolved solid can be conveniently analysed by the method. The direct sensing of As(iii ) as well as As(v ), the use of benign and easily available chemicals, the absence of any hazardous by-product, undiminished applicability in sunlight, the testing procedure lasting only for about 30 min, and rapidity are the major advantages of the method. Thus, the method is potentially well-suited for the on-site testing of groundwater potability under different regulations.